Teacher Readiness In Coastal Areas Of Banten To Handle Post-Natural Disaster Trauma - Handoyo, Alfiandy Warih; Arga Satrio Prabowo; Dwi Rindiyani (Coution: Journal Counseling and Education, 2025)
Banten is a province with a fairly high potential for natural disasters. Natural disasters can cause trauma. Trauma if not handled properly will cause Post Traumatic Stress Disorder and even spread across generations. The handling of trauma and the impact of natural disasters that is quite effective in Indonesian society is school/education-based because all Indonesian citizens experience the learning process at various levels. Teachers must be prepared to handle child trauma as part of disaster mitigation. This study aims to map the condition of teacher readiness in dealing with traumatized children as part of a more comprehensive disaster mitigation effort. This study used a survey method with a sample of 100 teachers who were taken accidentally when school-based disaster management skills training activities were held. The research data were processed descriptively. The results of the study showed that the calling home indicator data was at 75% and was in the good category, relation building at 85% or in the very good category, emergency at 67% was in the good category, school trauma at 40% was in the sufficient category, and finally Assessment 15% was in the very poor category.